2021
DOI: 10.1186/s13018-021-02485-4
|View full text |Cite
|
Sign up to set email alerts
|

Age at surgery is correlated with pain scores following trochlear osteotomy in lateral patellar instability: a cross-sectional study of 113 cases

Abstract: Background A trochlear osteotomy aims to restore patellar stability in patients with recurrent patellar instability and trochlear dysplasia. The age of patients at time of surgery could be a relevant factor which influences outcome. We hypothesized that lower age at time of surgery is associated with better patient-reported outcomes. Methods A retrospective study was conducted on patients with patellar instability and trochlear dysplasia. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Additionally, in the present study, an older age was associated with a poor outcome in most functional scores and acted together with calcium in influencing postoperative Kujala and KOOS pain score. In line with the current study, Sambeeck et al [ 36 ] indicated that age was correlated with an increased pain score at rest. Ling et al [ 6 ] noted age as a variable of biggest relative importance in a multivariable model predicting for a recurrent dislocation.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, in the present study, an older age was associated with a poor outcome in most functional scores and acted together with calcium in influencing postoperative Kujala and KOOS pain score. In line with the current study, Sambeeck et al [ 36 ] indicated that age was correlated with an increased pain score at rest. Ling et al [ 6 ] noted age as a variable of biggest relative importance in a multivariable model predicting for a recurrent dislocation.…”
Section: Discussionsupporting
confidence: 92%
“…Postoperative outcomes included reoperations, recurrent patellar instability, 10-point Visual Analog Scale (VAS) knee pain at rest, 10-point VAS knee pain during sports/physical activity, 100-point VAS satisfaction with the index procedure [28][29][30], Kujala Anterior Knee score, MPFL-Return to Sport after Injury (MPFL-RSI) score, return to sport, and return to work. For the MPFL-RSI instrument, a score > 56 was considered a passing score indicating psychological readiness to return to sport [10].…”
Section: Postoperative Outcomesmentioning
confidence: 99%